Mutational analysis of a South African haemophilia B population - Bester, Chené (University of the Free State, 2023)
Introduction and Aim: Haemophilia B is an X-linked recessive bleeding disorder characterised by a deficiency of coagulation factor IX (FIX), due to a wide spectrum of causative mutations in the FIX encoding gene (F9). Based on the plasma concentration of normal FIX coagulant activity (FIX:C), haemophilia B can be classified as mild (>5 – <40 international units per decilitre (IU/dL)), moderate (1 – 5 IU/dL) or severe (<1 IU/dL). Genetic testing is an important aspect in the haemophilia B diagnostic approach and appropriate patient management. Given the low prevalence, haemophilia A and B are considered orphan diseases; however, because haemophilia B is much rarer than haemophilia A, it is a disorder that is often neglected in terms of basic research, resulting in suboptimal disorder management. The aim of this study was to screen haemophilia B patients in our region for known and novel F9 causative gene variants, as well as determine the genotype/phenotype relationship for each study participant. Methods: A total of 21 participants were enrolled in this study. All the participants were screened using conventional PCR assays to amplify F9 exon 1 – 8, followed by direct Sanger sequencing to analyse and confirm causative F9 gene variations. The F9 variants identified were compared to various F9 gene variants databases to confirm known and novel variants. Furthermore, for the functional analysis a FIX one-stage and an enzyme-linked immunosorbent assay (ELISA) assay were done to measure the FIX:C. Discrepancies between the ELISA and one-stage assay were determined by calculating the p-value. The genotype/phenotype relationship was determined for the study participants and subsequently compared to previously published data. Results and Discussion: A total of eight pathogenic F9 variations were identified throughout the FIX protein domains: p.Ser‏⁴º⁶Leu, p.Glu²⁴¹*, p.Asn³⁹³del, p.Asn¹º⁴Metfs*31, p.Phe¹²¹Leufs*3, p.Lys‏⁴⁵⁹Serfs*24, ‏ p.Val²⁴³Phefs*2, and Thr⁸⁴Glufs*20. Approximately 63% of the variants detected were novel. The previously published variants identified in our study did correlate with previously published data. Conclusion: The discovery of novel F9 pathogenic variations in our South African population is an exciting finding, proving that genetic analysis of people with Haemophilia B is an important undertaking to better understand the pathogenesis of Haemophilia B in our population, and the wider sub-Saharan African population.‏
Dissertation (M.Med.Sc. (Human Molecular Biology))--University of the Free State, 2023
Keywords: Haemophilia B; factor ix (fix); fix gene (f9); mutational analysis; f9 conventional PCR assay; one-stage fix assay; fix Elisa assay; pathogenic variant